Combination of Diabetes Self-Management Education and Support Through Telehealth and Hypnotherapy Optimizes Self-Care Behaviors and Lowering HbA1c Levels in Patients with Type 2 Diabetes Mellitus: Combination of Diabetes Self-Management Education and Support - Subiyanto, Paulus; Saifulaman, Muhammed; Sitorus, Ratna (Journal of Tropical Life Science, 2025)
This study aims to explore the effectiveness of the combination of Diabetes Self-Management Education and Support (DSMES) through telehealth and hypnotherapy in optimizing self-care behavior and reducing hemoglobin A1c (HbA1c) levels in patients with type 2 diabetes mellitus (T2DM). The study used a quasi-experimental approach and comparative study with a pretest-posttest design and a 3-month cohort design. This study was conducted after obtaining a letter of ethical eligibility involving 40 T2DM patients divided into two groups. The control group received conventional medical services face-to-face. The intervention group received a DSMES program of seven self-care behaviors via telehealth with additional hypnotherapy sessions. The respondents in this study are women (60%) with an average age of 55.3 (31–65) years, who are highly educated (80%). A significant increase in DSM scores before and after the intervention occurred in the intervention group, (49.35–81.20) or (+31.85), and in the control group, (55.70–55.52) or (−0.18). The decrease in A1c in the intervention group (8.9%–7.37%) was (−1.53) and in the control group (8.12%–8.10%) was (−0.02). There were significant differences in DSM attainment and HbA1c levels in both types of interventions (p = 0.000; p = 0.030 with alpha 5%). DSMES, through telehealth combined with hypnotherapy, can provide a synergistic effect with medical treatment commonly given to patients with T2DM during and after the COVID-19 pandemic. This approach not only improves healthcare accessibility but also addresses the psychological barriers associated with lifestyle change.